2020
DOI: 10.1021/acsomega.0c02090
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Electrochemical Oxidation on the Maturation Process of the Distilled Spirit

Abstract: Optimizing the aging process is urgently required in the distilled spirit industry because of the time-consuming and expensive procedure of natural aging. Herein, the componential changes of the liquor sample are confirmed by the component analysis (e.g., gas chromatograph), and the effect of electrochemical oxidization treatment on the overall properties of typical Chinese liquor (Baijiu) is investigated. The key finding is that high oxidative potential can be used to catalyze the oxidation of alcohols, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In our previous study, the impact of electrochemistry on the overall properties of liquor was confirmed ( Xiong et al, 2020 ; Zheng et al, 2021 ). Therefore, we further examined the influence of the electrochemical treatment on the interconversion relationship between those components and the overall aroma of liquor.…”
Section: Resultsmentioning
confidence: 71%
“…In our previous study, the impact of electrochemistry on the overall properties of liquor was confirmed ( Xiong et al, 2020 ; Zheng et al, 2021 ). Therefore, we further examined the influence of the electrochemical treatment on the interconversion relationship between those components and the overall aroma of liquor.…”
Section: Resultsmentioning
confidence: 71%
“…The oxidation-based process holds a crucial position on the flavor formation of aged Baijiu. Natural aging includes a diversity of compound transformation, but the oxygen-based process is performed similar to electrochemical oxidation ( Xiong et al, 2020 ). Three-electrode electrochemical system combined with ultrahigh performance liquid chromatography quadrupole-orbitrap high resolution mass spectrometry was used to investigate the oxidation-based flavor formation mechanism.…”
Section: Molecular Mechanisms Of Baijiu Agingmentioning
confidence: 99%
“…Electrochemical methods have been a powerful tool to discriminate aged Baijiu with the advantage of no other sample preparation technique ( Xiong et al, 2020 ). Moreover, electrochemical technologies could be more compatible to the analysis of Baijiu that without the addition of any redox-active agents.…”
Section: Discrimination Of Baijiu Vintagementioning
confidence: 99%
“…The most prized whiskies are aged for decades in casks, increasing their flavor profile and expense dramatically. Many less-expensive, younger whiskies are often blended with a small portion of aged spirit to add depth of flavor, and researchers are exploring ways to chemically recreate this “aged” flavor profile. , Thus, simply knowing the age of a single cask is not enough to judge how the contents have chemically aged, and how it might fit into a final product. Constant sampling of casks by highly experienced master blenders is required to monitor the progress of whisky aging, across hundreds or thousands of casks.…”
Section: Introductionmentioning
confidence: 99%